ChemInform Abstract: Oxidation of Aminoalkyl and Hydroxylaminoalkyl Furans. Issue 14 (March 2016) - Kazancioglu, Mustafa Zahrittin; Akin Kazancioglu, Elif; Secen, Hasan; Altundas, Ramazan
Abstract: The novel photooxygenation of furan derivatives provides ozonide‐like intermediates.